Hellison Model Hybridation with Project Based Learning (Pjbl) on Responsibility in Online Learning - Defri Mulyana; Deni Setiawan; Randy Fadillah Gustaman (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2022)
The importance of fostering responsible attitudes during online learning so that students' responsible attitudes can be formed through the habit of carrying out responsible behavior. Through practice-based course learning, it is hoped that students' attitudes of responsibility will be better. Because in practice-based courses not only aspects of skills are developed, but the formation of other aspects is developed in it through movement activities. The need for a learning model with an online concept that matches the characteristics of the student's attitude of responsibility so that the problems encountered can be handled appropriately.The researcher tried to unite the Hellison learning model and the Project Based Learning (PBL) model, considering that the researcher chose the helison model, which is one of the social reconstruction models that is suitable for problems regarding the attitude of responsibility, from the results of data analysis in this study, the probability value (sig. ) for responsibility is 0.000 < 0.05. Thus, H0 is rejected, meaning that the Hybridization of the Hellison and PjBL models between the before and after tests has a significant effect on responsibility in the experimental group. Thus the Hellison model and the PjBL learning model are applied to foster students to understand the attitude of responsibility when participating in learning and practice a sense of personal responsibility (self-responsibility) which is packaged in a practice-based online learning.